2019
DOI: 10.1016/j.coastaleng.2019.103505
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of tsunami induced scour at onshore structures

Abstract: Tsunami inundation of the coastal environment can induce scour at structure foundations leading to failure. A series of experiments are made using a unique Pneumatic Long Wave Generator to generate tsunami wave periods of 25-147 s equating to 3-17.3 mins at 1:50 Froude scale. The waves propagate over a sloping bathymetry and impinge upon a square structure founded onshore in a at sediment bed. Flow velocity, height and scour are recorded as a function of time during tsunami inundation. The rate of scour is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…A well-documented failure mode of sea walls during the TET was that of foundation scour at the landward toe of the walls from overtopping flows (e.g., EEFIT, 2011, EEFIT, 2013and Chock et al, 2013. Scour depth and intensity is sensitive to flow velocity and inundation time, as observed by McGovern et al (2019) for flow past partially blocking structures. Further studies of overtopping flow and landward toe and foundation scour would be useful.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A well-documented failure mode of sea walls during the TET was that of foundation scour at the landward toe of the walls from overtopping flows (e.g., EEFIT, 2011, EEFIT, 2013and Chock et al, 2013. Scour depth and intensity is sensitive to flow velocity and inundation time, as observed by McGovern et al (2019) for flow past partially blocking structures. Further studies of overtopping flow and landward toe and foundation scour would be useful.…”
Section: Discussionmentioning
confidence: 98%
“…Tsunami may also inundate without a significant bore front. Field (ASCE, 2022) and experimental (McGovern et al, 2019) measurements have shown that maximum tsunami overland velocities are often found at approximately 2/3 of the maximum tsunami height ℎ 𝑖 , and at approximately 1/3 of the tsunami period 𝑇 . While there are several design methods that include tsunami onshore effects such as Goda et al (2014), FEMA (2000) and ASCE (2022), for the specific case of sea defences, engineers still have access to relatively limited and disparate data and guidance on tsunami forces.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, scour holes were observed in areas that were normally not at risk of scour (onshore piles located approximately 100 m or more from the shoreline). The prediction of scour at onshore locations during extreme inundation events (e.g., hurricane or tsunami) is not as common or as researched compared with scour in riverine or offshore environments (Borga et al 2017;McGovern et al 2019). McGovern et al (2019) tackled this gap in knowledge by designing experiments with a specialized pneumatic long-wave generator and a detailed laboratory setup in order to observe scour development in real time, albeit scaled down to a 1:50 Froude scale.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of scour at onshore locations during extreme inundation events (e.g., hurricane or tsunami) is not as common or as researched compared with scour in riverine or offshore environments (Borga et al 2017;McGovern et al 2019). McGovern et al (2019) tackled this gap in knowledge by designing experiments with a specialized pneumatic long-wave generator and a detailed laboratory setup in order to observe scour development in real time, albeit scaled down to a 1:50 Froude scale. Borga et al (2017) determined that only two equations adequately described scour around a building foundation (and not a slender pile) resulting from storm surge using the flow, building, and soil characteristics as input parameters.…”
Section: Introductionmentioning
confidence: 99%
“…10.1029/2020WR028970 2 of 17 The propagation of bores is known to play a significant role relating to sedimentary motion, even though the main driving mechanism of incipient motion has been previously described from flow velocity measurements, bed evolution, and visualization (Jiyu et al, 1990;Losada & Desiré, 1985;McGovern et al, 2019;Reungoat et al, 2018). To understand the actual phenomena of incipient motion during the tidal bore, more in situ comprehensive study is required which simultaneously measures free water surface, velocities and both horizontal and vertical forces, and which also uses visualization.…”
Section: Introductionmentioning
confidence: 99%